The Exemplary Approach of Islamic Religious Education Teachers in Fostering Emotional Spiritual Quotient - Mohammad Usman; Muhammad Zainuddin; Muhammad In’am Esha (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to gain an understanding of Islamic Religious Education Teachers' exemplary approach to developing students' emotional, spiritual quotients. This article employs a qualitative research methodology in conjunction with a case study approach. The approach taken is consistent with the formulation of the problem under investigation. Informants were chosen based on the research's objectives. Formal and informal interviews were conducted. The findings of this study demonstrate two aspects of the emotional approach in Islamic education: Methods of persuasion and education. Teachers develop spiritual, emotional intelligence by providing students with new knowledge that includes exemplary figures dating all the way back to the Prophet Muhammad's time and exemplary national figures, as well as by inviting students to practice family strategies for recognizing and managing their own emotions, the ability to motivate themselves, the ability to recognize the emotions of others, and how to build relationships with others.